Temperature effects on the mobility of pyramidal < c + a > dislocations in magnesium. (15th January 2017) - Fan, Haidong; Wang, Qingyuan; Tian, Xiaobao; El-Awady, Jaafar A.
Abstract: Temperature effects on the mobility of < c + a > dislocations on pyramidal planes are characterized by molecular dynamics simulations. On the first-order pyramidal planes, near-edge dislocations always decompose, while the critical resolved shear stress (CRSS) for near-screw dislocations increases with increasing temperatures. On the second-order pyramidal planes, the CRSS decreases to a minimum at 400 K, then increases with temperatures. This indicates that first-order pyramidal slip is favorable at low temperatures, while at elevated temperatures both pyramidal slip planes are active, leading to profuse plasticity. Graphical abstract: